Peran Metode Qira’ah dalam Meningkatkan Literasi Bahasa Arab di Prodi Pendidikan Bahasa Arab - Fidani, Riki; Ghifary, Muhamad Fadlan; Indriana, Dina; Ulya, Aqil Sajidil (Al Maghazi : Arabic Language in Higher Education, 2023)
Many Arabic language education students in Arabic language education programs lack literacy, making it difficult to understand the language they are taking in their study program. so that the qira’ah method must be applied to increase language literacy found by many Arabic language students but they do not understand what they are learning, qiraah is the main method for a broader understanding in the field of language. This study aimed to the role of the Qira’ah Method in Increasing Arabic Literacy in Arabic Language Education Study Programs. The method used qualitative study and collecting data used interview and observation. The result showed that language functions can be developed and implemented in everyday life as well as in the academic campus of the Arabic Language Education Program. Keywords: Arabic Education Programs, Arabic Literacy, Qira’ah Method